2022
DOI: 10.1111/tbed.14694
|View full text |Cite
|
Sign up to set email alerts
|

Co‐circulation of coronavirus and avian influenza virus in wild birds in Shanghai (2020–2021)

Abstract: Co‐infection of SARS‐CoV‐2 and influenza viruses has been reported worldwide in humans. Wild birds are natural reservoir hosts for coronaviruses (CoVs) and avian influenza viruses (AIVs). It is unknown whether co‐infection with these two types of viruses occurs in wild birds. In this study, the prevalence of co‐infection with CoV and AIV in wild birds in Shanghai, China during 2020–2021 was investigated by detecting these viruses in cloacal, tracheal, and faecal samples. Results showed that the overall rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…and Charadriformes [ 10 , 11 , 12 ]. However, Gammacoronavirus tends to be detected in domestic birds, while Deltacoronavirus infects both domestic and wild birds [ 13 , 14 ]. Two CoVs isolated from cetaceans have also been placed in the genus Gammacoronavirus [ 15 , 16 ], and Deltacoronavirus has also been found in pigs (porcine deltacoronavirus -PDCoV), causing acute diarrhea and dehydration [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…and Charadriformes [ 10 , 11 , 12 ]. However, Gammacoronavirus tends to be detected in domestic birds, while Deltacoronavirus infects both domestic and wild birds [ 13 , 14 ]. Two CoVs isolated from cetaceans have also been placed in the genus Gammacoronavirus [ 15 , 16 ], and Deltacoronavirus has also been found in pigs (porcine deltacoronavirus -PDCoV), causing acute diarrhea and dehydration [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 2022 study by Marchenko et al of samples taken from wild waterfowl of the Novosibirsk region revealed only one deltacoronavirus in a Gadwall collected in 2020, while the phylogeny of gammacoronaviruses and their hosts were revealed as miscellaneous [23]. Nevertheless, similar studies in wintering sites in China revealed a large prevalence of deltacoronaviruses [32]. At the same time, gammacoronaviruses were also found there, mainly in wild ducks, whereas deltacoronaviruses were found mainly among the Ciconiiformes and Columbiformes, which are the dominant resident bird orders in wintering places in eastern China (Shanghai), but they were not represented in our studies.…”
Section: Discussionmentioning
confidence: 98%
“…For the first time, we showed co-infection with avian coronavirus and paramyxovirus (0.8%). Previous research in China revealed co-infections of ACoV and AIV and that the presence of co-infected birds was relatively high (3.3%) [ 32 ]. The highest proportion of individual birds with multiple co-infections in our study was shown for Common Teals ( Anas crecca ) (n = 51, 28.3%), which had the highest diversity of combinations.…”
Section: Discussionmentioning
confidence: 99%
“…The H13 subtype avian influenza virus isolated from wild birds in China was able to replicate in both chickens and mice ( Sun et al, 2023 ). As the host of a variety of coronaviruses, wild birds play a role in the cross-species transmission of coronaviruses from birds to mammals ( Michelle and Holmes, 2020 ), and a recent study confirmed that coronaviruses increase the susceptibility of wild birds to avian influenza viruses ( Ma et al, 2022 ). The conclusion of these similar studies gives an indication of the risk of pathogens from wild waterfowl crossing the host barrier to infect poultry or mammals.…”
Section: Discussionmentioning
confidence: 99%